2011
DOI: 10.3390/molecules16075315
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Extraction Process and In Vivo Inhibitory Effect of Ganoderma Triterpenes in Oral Mucosa Cancer

Abstract: The aim of the reported study was to optimize the extraction process for ganoderma triterpenes and to investigate the in vivo inhibitory effect of ganoderma triterpenes on the genesis and progression of oral cancer. Single-factor and orthogonal methods were used to investigate the effects of extraction solvent, solvent amount, extraction time, extraction temperature, and number of extractions, on the extraction rate for ganoderma triterpenes. A golden hamster model with cheek pouch dynamic canceration was esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 1 publication
3
13
0
Order By: Relevance
“…UA per g dw was obtained. These claims have been supported by other authors 36 who reported that the extraction of Tr from G. lucidum is largely influenced in the T range between 80 and 100°C and if prolonged time-cycles of 2 h (∼4 cycles) are used.…”
Section: Extraction Efficiency By Using the Soxhlet Techniquesupporting
confidence: 53%
“…UA per g dw was obtained. These claims have been supported by other authors 36 who reported that the extraction of Tr from G. lucidum is largely influenced in the T range between 80 and 100°C and if prolonged time-cycles of 2 h (∼4 cycles) are used.…”
Section: Extraction Efficiency By Using the Soxhlet Techniquesupporting
confidence: 53%
“…The different extraction methods of Lingzhi triterpenes mainly include (1) extraction with methanol or ethanol as the solvent, followed by direct separation of the extracts; (2) extraction by methanol or ethanol, followed by separation of the total acid portion by alkali treatment and separation of Lingzhi triterpene; and (3) extraction of the total acid portion by ether, followed by diazomethane methylation and then separation. Extraction of Lingzhi triterpene using ethanol is the easiest approach to maintain the activity of the extracts and to scale up its production (Gao et al 2011). In addition, in order to enhance the rate of extraction of triterpenes and shorten the extraction time, the ultrasonic technique was often used for treatment of raw materials (fruit body or spore) in the production, which would destroy the dense structure of Lingzhi cells.…”
Section: Development Of Ganoderma-based Productsmentioning
confidence: 99%
“…The total triterpenoid content was determined according to the report previously with some modification (Gao et al 2011), by using ultraviolet-visible spectrophotometry (UV-1800 UV/VIS spectrometer, Shimadzu, Tokyo, Japan) with ganoderic acid A as the control and 5% glacial acetic acid-vanillin solution and perchloric acid as the developer. The total triterpenoid content in GTs was calculated as milligrams of ganoderic acid A equivalents (GAAEs) per gram of GTs.…”
Section: The Total Triterpenoid Content In Gtsmentioning
confidence: 99%